THE EFFECT OF GRAVITY-DRIP FILTRATION METHODS ON THE CHEMICAL AND SENSORIAL PROPERTIES OF COFFEE (COFFEA ARABICA L. VAR. CASTILLO) - Zapata, Angela María Ormaza; Arango, Felix Octavio Díaz; Rojano, Benjamín Alberto (Coffee Science - ISSN 1984-3909, 2019)
Coffee prepared via gravity-drip filtration is an alternative to obtain varied sensorial profiles and determine the acidity, bitterness, and body thereof. In the present study, the retention of certain bioactive components was determined, as was the antioxidant activity and cup profiles for coffee beverages prepared by way of seven different gravity-drip filtration methods. The methods which registered the greatest bioactive metabolite retention were the Vietnamese, Clever, and RS 16 methods. The greatest hydroxycinnamic acid content was obtained with the Clever, Yama, Vietnamese, and V60 methods, in descending order. Antioxidant capacity was proportional to the retention of bioactive components, by way of ABTS and ORAC techniques, in the beverages prepared. The V60 and V60 Kalita methods retained the lowest amounts these compounds and their activity. The most predominant hydroxycinnamic acid in the seven evaluated preparations was chlorogenic acid. In accordance with consumer preferences, which seek functional food, it is recommended that coffee be consumed using the Clever or Vietnamese preparation methods, which present fuller body and enhanced bitter notes. In their absence, the RS 16 method is suggested, which presents a sensorial profile identical to that of the U.G.Q. pattern, with less intensity of bitterness.